The new challenge of “exercise + X″ therapy for Duchenne muscular dystrophy—Individualized identification of exercise tolerance and precise implementation of exercise intervention - Su, Yuhui; Song, Yafeng (Frontiers in Physiology, 2022)
Duchenne muscular dystrophy(DMD) is an incurable X-linked recessive fatal muscular disease.The mdx mouse model is the most common animal model of DMD,but the conclusions of animal experiments are not consistent.There are many conclusions such as beneficial exercise,harmful exercise or diffrent exercise effects.Due to the injury of DMD mainly occurs in skeletal muscle,so the body is very vulnerable to exercise tolerance, muscle contraction type,exercise time, exercise intensity, exercise object and other exercise intervention factors have great influence on the efficacy of exercise.At present, the mainstream treatment methods for DMD are gene therapy,cell therapy and drug therapy.Animal and human experiments suggested that appropriate exercise may improve the effect of such precision medical tools, thereby enhancing the muscle quality of patients and improving the muscle function of patients.However, animal volume may be an important factor affecting the efficacy of exercise.The efficacy of mdx mice is difficult to achieve in larger animals.Due to the skeletal muscle damage of DMD individuals,there are still many controversies about whether DMD animals or patients can exercise,how to exercise, when to exercise best,and how to exercise effect.Therefore, DMD mode,intensity and time range that DMD can withstand for exercise therapy are very limited.This paper aims to summarize and explore the scientific basis and efficacy of exercise as an adjuvant therapy for DMD gene therapy,cell therapy and drug therapy, and put forward the theoretical framework and optional strategies of ‘ exercise + X ’ combination therapy.